202k views
3 votes
Which is equivalent to (2^-3)^4

1/2^12

2

-2^12

1/2^7

1 Answer

3 votes

Answer:

The answer is First option

1/2^12 .


(1)/(2^(12) )

Explanation:

Given:

(2^-3)^4

i.e


(2^(-3) )^(4)

To Find:


(2^(-3) )^(4)=?

Solution:

Law of Indices


(x^(a)) ^(b) =x^(a* b)\\and\\x^(-1)=(1)/(x)

Using the above Property we get


(2^(-3) )^(4)=2^(-3* 4) \\\\ (2^(-3) )^(4)=2^(-12) \\\\(2^(-3) )^(4)= (1)/(2^(12) )

The answer is First option

1/2^12 .


(2^(-3) )^(4)=(1)/(2^(12) )

User Adham Amiin
by
4.9k points